1997
DOI: 10.1073/pnas.94.22.12186
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of syntaxin-mediated protein interactions blocks neurotransmitter secretion

Abstract: The membrane protein syntaxin participates in several protein-protein interactions that have been implicated in neurotransmitter release. To probe the physiological importance of these interactions, we microinjected into the squid giant presynaptic terminal botulinum toxin C1, which cleaves syntaxin, and the H3 domain of syntaxin, which mediates binding to other proteins. Both reagents inhibited synaptic transmission yet did not affect the number or distribution of synaptic vesicles at the presynaptic active z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 42 publications
10
75
3
1
Order By: Relevance
“…However, the three sites necessary for binding and cleavage by Bot N/C (Schiavo et al, 1995;O'Connor et al, 1997), which are present on Nt-Syr1 (Leyman et al, 1999) and associated with sensitivity to the toxin, are poorly conserved in OSM1/SYP61 ( Figure 12B). Although it remains unproven that OSM1/SYP61 is not sensitive to Bot N/C, this finding suggests that there may be another Arabidopsis SNARE protein that has a similar function, because Leyman et al (1999) were able to inhibit ABA-induced Cl Ϫ channel current in tobacco guard cells with Bot N/C treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the three sites necessary for binding and cleavage by Bot N/C (Schiavo et al, 1995;O'Connor et al, 1997), which are present on Nt-Syr1 (Leyman et al, 1999) and associated with sensitivity to the toxin, are poorly conserved in OSM1/SYP61 ( Figure 12B). Although it remains unproven that OSM1/SYP61 is not sensitive to Bot N/C, this finding suggests that there may be another Arabidopsis SNARE protein that has a similar function, because Leyman et al (1999) were able to inhibit ABA-induced Cl Ϫ channel current in tobacco guard cells with Bot N/C treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting as well that syntaxin appears to be required for tethering to membrane sites of the Ca 2ϩ channel that affects neurotransmitter release, ensuring G-protein OSM1/SYP61, Arabidopsis; STX6_MOUSE, syntaxin 6 from mouse; STX6_HUMAN, syntaxin 6 from human; STX10_HUMAN, syntaxin 10 from human. Sequences shown above the aligned sequences are two predicted Clostridium botulinum toxin C1 recognition sites (FMEEFFEQVE and ELEDMLESGN, respectively) and a cleavage site (AVKYQSKAR) from squid syntaxin (Schiavo et al, 1995;O'Connor et al, 1997). (C) Sequence alignment in the t-SNARE coiled-coil domain.…”
Section: Discussionmentioning
confidence: 99%
“…These toxins act as proteases that cleave one of the SNARE proteins, either syntaxin, SNAP-25 or synaptobrevin. 3 These and other observations 4,5 indicate that the proteins of the 7S complex are necessary for neurotransmitter release. Is there similar experimental data to support a role for the additional proteins of the 20S complex, SNAP and NSF, in neurotransmitter release?…”
mentioning
confidence: 86%
“…Binding of Clostridium neurotoxins and toxin cleavage of Syntaxin 1 or Synaptobrevin 1 blocks neurotransmitter release (Montecucco & Schiavo, 1995) but does not affect the number of vesicles docked at the nerve terminals. Cleavage of SNAP-25 by BotN\A affects only the late, Ca# + -dependent stages of exocytosis (Banerjee et al, 1996b ;O'Connor et al, 1997). Shiavo et al (1997) have suggested that, once docked, the Ca# + -dependent ' clamp ' effected by Synaptotagmin might bridge the primed SNARE complex.…”
Section: New Perspectives On Snare Functionmentioning
confidence: 99%
“…The larger part of each toxin comprises a permease that mediates transfer of the toxin protease across the plasma membrane. Each toxin then cleaves a unique protein target (Schiavo et al, 1992 ;Blasi et al, 1993 ;Binz et al, 1994 ;Yamasaki et al, 1994a-c) and this specificity has provided a remarkably powerful set of tools for probing SNARE function both in vitro (Hayashi et al, 1994) and in vivo (O'Connor et al, 1997 ;Stanley & Mirotznik, 1997).…”
Section: Snares and Associatesmentioning
confidence: 99%